Novel insights into cuproptosis inducers and inhibitors - Zhang, Ligang; Deng, Ruiting; Liu, Lian; Du, Hongli; Tang, Dongsheng (Frontiers in Molecular Biosciences, 2024)
Cuproptosis is a new pattern of Cu-dependent cell death distinct from classic cell death pathways and characterized by aberrant lipoylated protein aggregation in TCA cycle, Fe-S cluster protein loss, HSP70 elevation, proteotoxic and oxidative stress aggravation. Previous studies on Cu homeostasis and Cu-induced cell death provide a great basis for the discovery of cuproptosis. It has gradually gathered enormous research interests and large progress has been achieved in revealing the metabolic pathways and key targets of cuproptosis, due to its role in mediating some genetic, neurodegenerative, cardiovascular and tumoral diseases. In terms of the key targets in cuproptosis metabolic pathways, they can be categorized into three types: oxidative stress, mitochondrial respiration, ubiquitin-proteasome system. And strategies for developing cuproptosis inducers and inhibitors involved in these targets have been continuously improved. Briefly, based on the essential cuproptosis targets and metabolic pathways, this paper classifies some relevant inducers and inhibitors including small molecule compounds, transcription factors and ncRNAs with the overview of principle, scientific and medical application, in order to provide reference for the cuproptosis study and target therapy in the future.